The Utilization of Flashcards in Teaching English Vocabulary to Young Learners - Agnesia, Wega Dhea; Nurwadi, Nurul Fadilah; Suharyadi, Suharyadi; Anugerahwati, Mirjam; Khoiri, Niamika El (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study aims to investigates the effectiveness of using flashcards to teach English vocabulary to young learners. The research was conducted at SDN Gempol 2 with 36 third-grade students. A one-group pre-experimental design was employed, using pre-test and post-test to collect the data. The results revealed a significant improvement in students' vocabulary mastery, with the average score increasing from 65.83 (pre-test) to 76.80 (post-test). Statistical analysis showed that the t-value (11.056) exceeded the critical value (2.035), and the significance level (p = .000) was below the threshold of 0.05, indicating a meaningful difference. These findings suggest that flashcards are an effective tool for enhancing vocabulary acquisition among young learners, as they help maintain students’ engagement through visual and interactive learning.